Anatomy and Pathophysiology of Upper Airway Obstructive Sleep Apnoea: Review of the Current Literature - Shi Nee Tan (Sleep Medicine Research, 2021)
The increasing prevalence of obstructive sleep apnoea (OSA) led to the need to understand upper airway (UA) anatomy and its contribution to the disease process. This review article summarises the current understanding of OSA development in adults. It focuses on UA anatomy and pathophysiology in anatomical subsites including the nasal cavity, soft tissue, and bony frameworks. This article also describes research trends in the context of anatomy. The research investigated pathophysiological phenotypes and their correlation with anatomy, phenotype labelling using drug-induced sleep endoscopy and their clinical characteristics, and recent updates regarding non-invasive tools for diagnosing sites of obstruction in individuals with OSA.